Audyt kultury organizacyjnej na przykładzie firmy X - Tracz, Ewa (Organizational culture audit: firm X case, 2007)
Although an organizational culture is ubiquitous, it is difficult to be identified as well. In fact several different solutions for culture audit exist. Generally, they are combined with two diagnostic strategies: quantitative and qualitative. The article presents an example of culture assessment based on the qualitative approach and completed in Firm X.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 142-150